Dear Jester and other stories - Dāsa, Jagannātha Prasāda (Rupa, 2004)
The illusions of success -- Our daughter's happiness -- The inevitable -- The intimate stranger -- The Furlough -- The outsider -- Homeless -- Radha -- The homecoming -- The Bystander -- The Ultimatum -- Dear Jester